Impact of upwelling events on the sea water carbonate chemistry and dissolved oxygen concentration in the Gulf of Papagayo (Culebra Bay), Costa Rica: implications for coral reefs - Rixen, Tim (2012)
Abstract. The Gulf of Papagayo, Pacific coast of Costa Rica, is one of the three seasonal upwelling areas of Mesoamerica. In April 2009, a 29-hour experiment was carried out at the pier of the Marina Papagayo, Culebra Bay. We determined sea surface temperature (SST), dissolved oxygen concentration, salinity, pH, and the partial pressure of CO2 (pCO2). The aragonite saturation state (Ωa) as well as the other parameters of the marine carbonate system such as the total dissolved inorganic carbon (DIC) and the total alkalinity (TA) were calculated based on the measured pH and the pCO2. The entrainment of subsurface waters raised the pCO2 up to 645 μatm. SSTs, dissolved oxygen concentrations decreased form 26.4 to 23.7°C and from 228 to 144 μmol l-1. Ωa dropped down to values of 2.1. Although these changes are assumed to reduce the coral growth, the main reef building coral species within the region (Pocillopora spp. and Pavona clavus) reveal growth rates exceeding those measured at other sites in the eastern tropical Pacific. This implies that the negative impact of upwelling on coral growth might be overcompensated by an enhanced energy supply caused by the high density of food and nutrients and more favorable condition for coral growth during the non-upwelling season.